Explaining changes in Euro-Dollar positions: a study of banks in four European countries - Mills, Rodney H.
The study examines relationships between monetary factors and one type of short-term capital flow, namely, the borrowing and lending of Euro-dollars by commercial banks
osc 24/08/2021
Loans
Keywords: Euro-Dollars; Commercial Banking